STUDY OF IMPLEMENTATION OF PHARMACEUTICAL DESTRUCTION IN PHARMACIES IN DENPASAR CITY - Adilla, Farah (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 12 No 1 (2022): Indonesian Journal of Legal and Forensic SciencesDO - 10.24843/IJLFS.2022.v12.i01.p03, 2022)
Destruction of pharmaceutical preparations is one of pharmaceutical cares in Pharmacy which regulated in Permenkes RI No. 73 of 2016. The aim of this study is to describe the implementation of pharmaceutical care standard about destruction of pharmaceutical preparations in several pharmacies in Denpasar City. This study uses descriptive qualitative research through interviews. Data was collected by survey in 12 pharmacies in Denpasar City with 12 respondents on June 2020. This study uses total sampling technique in which the entire populations are used. Based on the identification results, the destruction of pharmaceutical preparations in majority of pharmacies are not in accordance with applicable regulation.